Association between serum cell adhesion molecules with hs-CRP, uric acid and VEGF genetic polymorphisms in subjects with metabolic syndrome - Ghazizadeh, Hamideh; Rezaei, Majid; Avan, Amir; Fazilati, Mohammad; Pasdar, Alireza; Tavallaie, Shima; Kazemi, Elham; Seyedi, Seyed Mohammad Reza; Ferns, Gordon A.; Azimi-Nezhad, Mohsen; Ghayour-Mobarhan, Majid (Molecular biology reports, 2020)
Metabolic syndrome (MetS) is associated with a pro-inflammatory state and endothelial dysfunction that places subjects with MetS at a higher risk of atherosclerosis. Inflammatory biomarkers are raised in patients at risk of developing cardiovascular diseases. In the current study, we aimed to examine the possible association between MetS and serum soluble adhesion molecules, hs-CRP, uric acid, and the genetic variations related to vascular endothelial growth factor (VEGF) gene. In this cross-sectional study, participants were enrolled from the Mashhad stroke and heart atherosclerotic disorders (MASHAD) study. The International Diabetes Federation criteria were used to define the MetS. Cell adhesion molecules (CAM) and serum hs-CRP were measured by ELISA and PEG-enhanced immunoturbidimetry method, respectively. We used a logistic regression analysis to determine independent associations of CAMs with the VEGF polymorphisms and MetS. Two hundred and 59 participants with and without MetS were enrolled. Participants with MetS and DM had a significantly higher serum E-selectin level (p < 0.05). Participants with a high serum E-selectin level had higher levels of hs-CRP, FBG, TG, uric acid, BMI and lower levels of serum HDL-C (p < 0.05). Interestingly, individuals with MetS with a genetic variant of the VEGF gene (rs6921438) had higher level of serum ICAM-1 (p = 0.04). There were significant associations between serum E-selectin concentrations and the presence of MetS, and its risk factors. Moreover, we demonstrated that MetS subjects with the rs6921438 genetic variant had a higher serum level of ICAM-1 (p < 0.05).